2003
DOI: 10.1542/peds.111.2.e168
|View full text |Cite
|
Sign up to set email alerts
|

Low Blood CD8+ T-Lymphocytes and High Circulating Monocytes Are Predictors of HIV-1-Associated Progressive Encephalopathy in Children

Abstract: ABSTRACT. Objective. Human immunodeficiency virus type 1 (HIV-1)-associated progressive encephalopathy (PE) is a common and devastating complication of HIV-1 infection in children, whose risk factors have not yet been clearly defined. Regardless of the age of presentation, PE shortens life expectancy. Paradoxically, as survival of patients has been prolonged as a result of the use of antiretroviral therapy, the prevalence of PE has increased. Therefore, a predictive marker of PE emergence is critical. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 48 publications
3
31
0
4
Order By: Relevance
“…In addition, levels of chemoattractants/ chemokines regulating monocytes/macrophage and T cell traffic are elevated in the CSF with HIV and SIV infection and correlate with the incidence of HAD (18,19). These observations support the putative role of activated monocytes and CD8 + T lymphocytes in regulating HIV-induced CNS disease (20).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, levels of chemoattractants/ chemokines regulating monocytes/macrophage and T cell traffic are elevated in the CSF with HIV and SIV infection and correlate with the incidence of HAD (18,19). These observations support the putative role of activated monocytes and CD8 + T lymphocytes in regulating HIV-induced CNS disease (20).…”
Section: Introductionsupporting
confidence: 52%
“…Once inflammation wanes, in a matter of days, macrophages are no longer detected in the CNS, and paralysis resolves. In the case of SIV and HIV, viral infection or loss of CD8 + T lymphocyte immune responses, or both, allow for a continued macrophage accumulation (3,20,63). It is possible that results from the CD8 depletion model represent a compression of the normal time frame seen in non-CD8-depleted animals and HIV-infected humans with CNS disease.…”
Section: Figure 10mentioning
confidence: 99%
“…Because it is well established that the best histopathologic correlate of HAD is the number of activated monocytes/ macrophages in the CNS 3 that are shown to migrate from the peripheral blood, 71,73 therapeutic strategies that inhibit processes of monocyte/macrophage transendothelial migration may thus be useful as an adjunctive therapy for HAD.…”
Section: Discussionmentioning
confidence: 99%
“…In general, higher CD4 cell counts, lower CD8 cell counts, and higher CD4:CD8 ratios have been associated with better neurobehavioral functioning [16]. However, contradictory data for adults [17] and children [18] have been presented. Tardieu et al [9] found that encephalopathy in the first year of life was associated with normal or high levels of CD4 + T lymphocytes, in contrast to later-onset encephalopathy, in which CD4 + T lymphocytes were deficient.…”
Section: H I V / a I D S M A J O R A R T I C L Ementioning
confidence: 99%